Dimensional stability improvements of waste wood flour/HDPE composites via carbon black network embedding. (13th September 2021) - Hao, Xiaolong; Sun, Jin; Chen, Chuanfu; Zhou, Haiyang; Li, Yuyu; Li, Wenjuan; Wang, Qingwen; Ou, Rongxian
Graphical abstract: Highlights: A continuous CB network was constructed in the WWPC. The dimensional stability of N-WWPC was improved compared with that of R-WWPC and WWPC control. Constructing CB network in WWPC is a facile and environmentally friendly way to pursue further advances of WWPC. Abstract: The insufficient dimensional stability of waste wood flour/high-density polyethylene composites (WWPC) remains a consistent limitation to its widespread utility. Accordingly, a visible rigid network based on nanoscale carbon black was established within WWPC for the development of deformation-resistant WWPC. Specifically, the carbon black was first subjected to activation and organic modification, then the modified carbon black was evenly distributed on the surface of WWPC pellets via mechanical mixing, and the resultant coated WWPC pellets were hot-pressed to form a network distributed WWPC where the carbon black was primarily located at the interfaces among WWPC pellets. Compared with the modified carbon black randomly distributed WWPC prepared by traditional melt-blending method, the network distributed WWPC exhibited better creep resistance, lower water absorption, and lower thermal-expansion at specific carbon black content, which indicated that the network distributed WWPC effectively resisted deformation caused by external forces, heat, and moisture. Additionally, due to the introduction of carbon black rigid network, the network distributed WWPC presented higher tensile modulus and comparable tensile and impact strength compared with the randomly distributed WWPC, and both WWPC exhibited higher mechanical properties than the carbon black-free WWPC control. These results confirmed that the formation of carbon black rigid network can improve the dimensional stability as well as the mechanical properties of WWPC.